Decavanadate Salts of Cytosine and Metformin: A Combined Experimental-Theoretical Study of Potential Metallodrugs Against Diabetes and Cancer - Sánchez-Lara, Eduardo; Treviño, Samuel; Sánchez-Gaytán, Brenda L.; Sánchez-Mora, Enrique; Eugenia Castro, María; Meléndez-Bustamante, Francisco J.; Méndez-Rojas, Miguel A.; González-Vergara, Enrique (Frontiers in Chemistry, 2018)
Cytosine, a DNA and RNA building-block, and Metformin, the most widely prescribed drug for the treatment of Type 2 Diabetes mellitus were made to react separately with ammonium or sodium metavanadates in acidic aqueous solutions to obtain two polyoxovanadate salts with a 6:1 ratio of cation-anion. Thus, compounds [HCyt]6[V10O28]•4H2O, 1 and [HMetf]6[V10O28]•6H2O, 2 (where HCyt = Cytosinium cation, [C4H6N3O]+ and HMetf = Metforminium cation, [C4H12N5]+) were obtained and characterized by elemental analysis, single crystal X-ray diffraction, vibrational spectroscopy (IR and Raman), solution 51V-NMR, thermogravimetric analysis (TGA-DTGA), as well as, theoretical methods. Both compounds crystallized in P1 ̅ space group with Z’ = 1/2, where the anionic charge of the centrosymmetric ion [V10O28]6- is balanced by six Cytosinium and six Metforminium counterions, respectively. Compound 1 is stabilized by π-π stacking interactions coming from the aromatic rings of HCyt cations, as denoted by close contacts of 3.63 Å. On the other hand, guanidinium moieties from the non-planar HMetf in Compound 2 interact with decavanadate μ2-O atoms vía N-H•••O hydrogen bonds. The vibrational spectroscopic data of both IR and Raman spectra show that the dominant bands in the 1000-450 cm-1 range are due to the symmetric and asymmetric ν(V─O) vibrational modes. In solution, 51V-NMR experiments of both compounds show that polyoxovanadate species are progressively transformed into the monomeric, dimeric and tetrameric oxovanadates. The thermal stability behavior suggests a similar molecular mechanism regarding the loss of water molecules and the decomposition of the organic counterions. Yet, no changes were observed in the TGA range of 540-580°C due to the stability of the [V10O28]6- fragment. Dispersion-corrected density functional theory (DFT-D) calculations were carried out to model the compounds in aqueous phase using a polarized continuum model calculation. Optimized structures were obtained and the main non-covalent interactions were characterized. Biological activities of these compounds are also under investigation. The combination of two therapeutic agents opens up a window towards the generation of potential metalopharmaceuticals with new and exciting pharmacological properties.